South African e-commerce logistics: Reproducing racialised capitalism through warehouse work - Bridget Kenny (Work Organisation, Labour and Globalisation)
Based on industry reports and interviews with warehouse workers and unions, this article examines how the global patterns of e-commerce logistics are integrated with and constituted through concrete relations of racialised labour processes in South Africa. It analyses the specificity of the growth of capital investment, the expansion of consumer markets, new state interests and the new use of digital technology in the labour process of e-commerce-based warehouse work in South Africa. Many new features of work organisation in warehouses are experienced by black workers through longer-term relations of surveillant racial despotism and limited employment futures. Scholarship on logistics globally, especially research purporting to explain the trajectory of workers’ politics at the local level, has tended to underestimate the articulation of logistics in time and space. In this article, we examine how histories of capital investment, a highly precarious racialised labour market, lack of skill recognition and union organising legacies reveal how continuities intertwine with new patterns of logistics.